A comprehensive theoretical approach for analysing manoeuvring effects on ships by integrating hydrodynamics and power system - Saman Nasiri; Saeed Peyghami; Mostafa Parniani; Frede Blaabjerg (IET Electrical Systems in Transportation)
Abstract Ship motions affect the propulsion system, which causes fluctuations in the power system. Mutually, the power system variations impact the ship velocity by generating speed changes in the propeller. Therefore, interconnecting the ship hydrodynamic and power system has paramount importance in designing and analysing an all‐electric ship (AES). The lack of an integrated model that can be evaluated in various operating conditions, such as manoeuvring, is evident. This paper explores the required perceptions for the power system and hydrodynamic analysis of an AES. Then, an integrated theoretical model comprising both the ship motion and power system is proposed. In addition to providing an accurate model for the ship in varying situations, this study demonstrates that the ship speed estimation during a ship route change differs from when the interconnections are overlooked. In the light of this determination, a straightforward enhancement for the ship speed control system is proposed. The effects of this modification on the ship power system are explored using the proposed model. The developed model is examined in different scenarios, and its advantages are discussed. It is shown that this model is suitable for employing in the model‐based design of AESs.